Experimental verification of an angle-sensorless control scheme for bearingless permanent magnet machines - Tobias WELLERDIECK (The Japan Society of Mechanical Engineers, 2017)
Bearingless machines are used for a variety of applications with demand for low mechanical loss, low wear and low contamination. These machines use contact-free magnetic suspension to levitate the rotor. The control of the machine requires precise radial and angular position information in order to ensure stable levitation. This information is usually obtained with two types of sensors: radial displacement sensors and angle sensors. Alternatively, an angle-sensorless control scheme can be used, reducing the complexity and the cost of the machine. While such a control is well known for conventional machines it is challenging to adapt it for bearingless machines. The reason is that most methods fail to provide the angle information at zero and at low speed but bearingless machines require knowledge about the rotor angle at all speeds in order to function. The theoretical mode of operation of a model based angle observer for zero and low speed operation of a bearingless machine was shown in previous publications. The observer obtains the rotor angle estimation error by analyzing the performance of the radial bearing and comparing it to the performance of a model with zero angle error. This observer can be used for operation at standstill and over the whole speed range. This paper provides a more detailed description of the non-idealities of the zero and low speed observer and presents results of machine operation without angle sensors. The generation of torque and force inside the machine is analyzed in more detail. Furthermore, it is shown how to combine the novel observer with a conventional, back electromotive force based, high speed angle observer. The experimentally verified results of this paper indicate that the novel observer can be used up to speeds at which back electromotive force estimation is possible. This allows the efficient, angle-sensorless operation of the machine over the whole speed range.